Frontier mission : a history of religion west of the Southern Appalachians to 1861 - Posey, Walter Brownlow, 1900-1988 (University of Kentuky Press, 1966)
In this first major study of religion in the South prior to the Civil War, Mr. Posey surveys the work of seven chief denominations -- Methodist, Baptist, Presbyterian, Disciples of Christ, Cumberland Presbyterian, Roman Catholic, and Protestant Episcopal -- as they developed in the present states of Kentucky, Tennessee, Alabama, Mississippi, Texas, Arkansas, Louisiana, and Missouri.